Process for catalytically coating scaffolds
Patent Information
- Application Number
- JP2021576137
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-21
- Filing Date
- 2020-05-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-05-11
Smart Images

Figure 0007631239000025 
Figure 0007631239000001 
Figure 0007631239000002
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE The present disclosure relates generally to a process for coating a scaffold, and in particular to a process for coating a scaffold in a static mixer using a catalytic liquid suspension. [Background technology]
[0002] A continuous flow chemical reactor generally comprises a tubular, duct, plate-type channel or chip-type channel reaction chamber into which a reactant fluid is continuously fed to undergo a chemical reaction and continuously form a product that exits the reaction chamber. The reaction chamber is usually heated electrically or by a recirculating heating / cooling fluid, for example in a shell-and-tube heat exchanger configuration, to facilitate heat transfer to / from the reaction.
[0003] Continuous flow reactors used in catalytic reactions typically employ packed bed reaction chambers, where the reaction chamber is packed with solid catalyst particles that provide a catalytic surface on which chemical reactions can occur. Static mixers are used to premix the fluid streams before contacting the packed bed reaction chambers and downstream of these chambers to transfer heat between the central and outer regions of the reaction tubes. Static mixers comprise solid structures that block the flow of fluids, which promotes mixing of the reactants prior to reaction in the packed bed reaction chambers and promotes a desired pattern of heat transfer downstream of these chambers.
[0004] There is a need for alternative and improved processes for catalytically coated scaffolds, and specifically static mixer scaffolds, that can provide a variety of desirable properties, such as the flexibility and utility of catalytic static mixer technology, which can provide more efficient mixing of chemical and / or electrochemical reactants, heat transfer, and catalytic reactions. Summary of the Invention
[0005] The present inventors have undertaken significant research and development of alternative catalyst deposition methods and have identified that they can provide a catalytic surface on the surface of a static mixer scaffold such that the resulting static mixer can be used in a continuous flow chemical reactor.
[0006] In one aspect, a process for preparing a catalytically coated scaffold is provided, comprising the steps of: (i) applying a catalytic liquid suspension to a surface of a scaffold to provide a coating comprising catalytically reactive sites on the surface of the coated scaffold, wherein the catalytic liquid suspension comprises a liquid carrier comprising a plurality of ex-situ catalyst particles, the coated scaffold having a non-line-of-sight configuration comprising a plurality of passages configured to disperse and mix one or more fluid reactants during their flow and reaction, and (ii) drying the coated scaffold to remove the liquid carrier and provide a coated scaffold comprising the ex-situ catalyst particles. In one embodiment, the scaffold may be a static mixer. In one embodiment, the surface of the static mixer may be pre-coated with a support material and optionally a binder prior to step (i). In one example, the catalytic liquid suspension further comprises a binder. In one embodiment, applying the catalytic liquid suspension to the surface of the scaffold in step (i) may be by wash coating or by dip coating.
[0007] In another embodiment, the process comprises a pre-treatment step prior to applying the catalytic liquid suspension to the surface of the scaffold in step (i), which pre-treatment step may be at least one surface treatment step to the surface of the scaffold selected from chemical treatment, anodizing, hot dip plating, vacuum plating, painting, thermal spraying, and acid etching.
[0008] In an embodiment, the catalyst particles are formed from a catalyst support material that includes a catalyst material on a support material or a catalyst material. The catalyst material can be selected from a metal, a metal oxide, an aluminum silicate, an activated carbon, a mesoporous carbon, a graphene, a graphite material, a metal organic framework, a zeolite, or any combination thereof. For example, the metal can be selected from at least one of aluminum, iron, cerium, calcium, cobalt, copper, magnesium, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or their metal oxides.
[0009] The catalyst support material may be selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel modified aluminum oxide silicon oxide, or zeolite.
[0010] The support material may be selected from at least one of activated carbon, mesoporous carbon, graphene, graphite materials, metal organic frameworks, zeolites, aluminum oxide, silicon dioxide, ceramics, magnesium chloride, calcium carbonate, or dipotassium oxide. When a catalytic material is used as the support material, the catalytic material and the support material will be different.
[0011] In one embodiment, the concentration of catalyst particles in the catalytic liquid suspension may be less than 10% by weight, based on the total weight of the catalytic liquid suspension.
[0012] In another embodiment, the binder for the catalytic liquid suspension may be selected from the group including hydroxypropyl cellulose, methyl cellulose, polyester, polyurethane, acrylic resin, condensation resin, polyvinyl acetate, sodium poly(acrylic acid), polyvinylidene fluoride, polyethylene oxide, polyethylene glycol, dextrin, sodium silicate, colloidal silica, polydimethylsiloxane, boehmite, colloidal aluminum oxide, or polyisobutylene. The binder may be added at a concentration of between about 0.3% and about 5% by weight, based on the total weight of the catalytic liquid suspension.
[0013] In one embodiment, the liquid carrier may be selected from the group including water, ethanol, isopropanol, butanol, ethyl acetate, acetone, or combinations thereof.
[0014] In one embodiment, the catalytic liquid suspension may have a solids content between about 3% and about 28% by weight. The thickness of the coating may be between about 1 μm and about 50 μm. The surface area of the catalyst may be between about 1 m 2 / g~about 1000m 2 The adhesion of the coating may result in a total mass loss of the coating of less than about 0.5 wt. % as measured by an ultrasonication test.
[0015] In one embodiment, the scaffold may be a metal, metal alloy, cermet, carbon fiber, silicon carbide, or polymer. In some examples, the scaffold may be a metallic scaffold. For example, the metal or metal alloy of the metallic scaffold is titanium, aluminum, or stainless steel.
[0016] In one embodiment, the aspect ratio (L / d) of the scaffold may be at least 75.
[0017] In another embodiment, the ex situ catalyst particles may be less than about 5 μm.
[0018] In one embodiment, the process may further include a drying step and / or an activation step. The drying step may include the steps of: (a) applying a first temperature in the range of about 15° C. to about 30° C. to the coated surface of the scaffold for a first period of about 4-24 hours to volatilize at least a portion of the volatile materials from the catalytic liquid suspension, and (b) applying a second temperature in the range of about 100° C. to about 180° C. under a controlled atmosphere for a second period of about 4-24 hours to form a dry coating on the surface of the scaffold.
[0019] In another aspect there is provided a catalytically coated scaffold prepared by the process for preparing a catalytically coated scaffold as defined herein.
[0020] In another aspect, a catalytically coated scaffold is provided that includes a coating on the scaffold, the coating comprising a plurality of catalytic particles, the coated scaffold having a non-line-of-sight configuration that includes a plurality of passageways configured for dispersing and mixing one or more fluid reactants during flow and reaction thereof, in one embodiment, the coating includes a support material and optionally a binder.
[0021] In one embodiment, the catalyst particles may be selected from metals, metal oxides, aluminum silicates, activated carbon, mesoporous carbon, graphene, graphite materials, metal organic frameworks, zeolites, or any combination thereof. The catalyst particles may be selected from at least one of aminium, iron, cerium, calcium, cobalt, copper, magnesium, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or metal oxides thereof.
[0022] In certain embodiments, the support material may be selected from at least one of activated carbon, mesoporous carbon, graphene, graphitic materials, metal organic frameworks, zeolites, aluminum oxide, silicon dioxide, ceramics, magnesium chloride, calcium carbonate, or dipotassium oxide.
[0023] In certain embodiments, the catalyst support material may be selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel modified aluminum oxide silicon oxide, or zeolite.
[0024] In certain embodiments, the binder may be selected from the group including hydroxypropyl cellulose, methyl cellulose, polyester, polyurethane, acrylic resin, condensation resin, polyvinyl acetate, sodium poly(acrylic acid), polyvinylidene fluoride, polyethylene oxide, polyethylene glycol, dextrin, sodium silicate, colloidal silica, polydimethylsiloxane, boehmite, colloidal aluminum oxide, or polyisobutylene.
[0025] In one embodiment, the catalyst particles may be less than 5 μm. The thickness of the coating may be between about 1 μm and about 50 μm.
[0026] In one embodiment, the coated scaffold may be a coated static mixer scaffold.
[0027] In another aspect, a continuous flow chemical reactor for use in the reaction of one or more fluid reactants is provided, the reactor comprising one or more catalytically coated scaffolds prepared by the process defined herein or catalytically coated scaffolds defined herein. The one or more fluid reactants may be provided as a continuous fluid stream. The continuous fluid stream may be provided by at least one liquid phase.
[0028] In another aspect, there is provided a continuous flow process for heterogeneous reactions comprising one or more chemical reactors as defined herein.
[0029] Preferred embodiments of the present disclosure will now be further described and illustrated, by way of example only, with reference to the accompanying drawings, in which: [Brief description of the drawings]
[0030] [Figure 1] Showing the route for coating static mixer scaffolds via options (a)-(d). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The present disclosure describes various non-limiting embodiments below, which relate to investigations conducted to identify alternative or improved processes for coating static mixer scaffolds that may provide various desirable properties, such as flexibility and availability of catalytic static mixer technology that may provide more efficient mixing, heat transfer and catalysis of chemical and / or electrochemical reactants. Surprisingly, it has been found that depositing catalytic materials on the surface of additively manufactured static mixers may provide efficient mixing, heat transfer and catalysis of reactants in continuous flow chemical reactors. It is understood that the catalytic deposition techniques described by the present invention may depend on the application and type of catalyst used. The inventors have surprisingly identified that the catalytic materials described herein provide improved catalytic deposition techniques for coating complex three-dimensional structures, such as static mixer scaffolds.
[0032] Compared to current heterogeneous catalytic systems such as packed beds, the static mixer of the present invention has been shown to offer various advantages. Although additive manufacturing techniques (i.e., 3D printing) allow flexibility in redesigning and configuring static mixers, there are other difficulties and challenges in providing a robust, commercially viable scaffold that can be catalytically coated to operate under certain operating performance parameters of a continuous flow chemical reactor, for example, to provide desirable mixing and flow conditions in a continuous flow reactor, as well as enhanced heat and mass transfer properties and reduced back pressure compared to packed bed systems.
[0033] Wash-coating and dip-coating techniques have been found to be surprisingly suitable for catalytically coating static mixer scaffolds and are suitable for use with a wide variety of catalytic materials.
[0034] Static mixers can be configured as scaffolding to provide inserts for use in in-line continuous flow reactor systems. Static mixers can also provide heterogeneous catalysis, which is critical to chemical manufacturing, a wide range of which includes the production of fine and specialty chemicals, pharmaceuticals, food and agrochemicals, consumer products, and petrochemicals.
[0035] General terminology Throughout this specification, unless specifically stated otherwise or the context requires otherwise, references to a single step, configuration of events, steps, or configurations of events shall be construed as including one and the plurality (i.e., one or more) of such steps, configurations of events, steps, or configurations of events. Thus, as used herein, the singular forms "a," "an," and "the" include plural aspects unless the context clearly dictates otherwise. For example, reference to "a" includes the singular as well as two or more, reference to "an" includes the singular as well as two or more, reference to "the" includes the singular as well as two or more, etc.
[0036] Those skilled in the art will understand that the disclosure herein may tolerate variations and modifications other than those specifically described. It is to be understood that the disclosure includes all such variations and modifications. The disclosure also includes all of the steps, features, compositions, and compounds referred to or shown in the present specification, individually or collectively, as well as any and all combinations of such steps or features, or any two or more of such steps or features.
[0037] Each embodiment of the present disclosure described herein is to be taken mutatis mutandis to every other embodiment unless specifically stated otherwise. The present disclosure is not to be limited in scope by the specific embodiments described herein, and such specific examples are intended for illustrative purposes only. Functionally equivalent products, compositions, and methods are clearly within the scope of the present disclosure, as described herein.
[0038] The term "and / or", e.g., "X and / or Y", shall be understood to mean either "X and Y" or "X or Y" and shall be interpreted as explicitly endorsing both meanings or either meaning.
[0039] Throughout this specification the word "comprise" or variations such as "comprises" or "comprising" will be understood to mean the inclusion of the stated scaffolds, integers or steps, or scaffolds, integers or steps, but not the exclusion of any other scaffolds, integers or steps, or scaffolds, integers or steps.
[0040] A number of prior art publications are referred to in this specification, but it will be expressly understood that no admission is made that any of these references form part of the general knowledge in the art in Australia or any other country.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs. Methods and materials similar or equivalent to those described herein can be used in the practice or testing of this invention, but suitable methods and materials are described below. In case of conflict, the present specification, including definitions, will take precedence. In addition, the materials, methods, and examples are merely illustrative and are not intended to be limiting.
[0042] Coating Process In one embodiment or example, a process for preparing a catalytically coated scaffold is provided, which includes the steps of: (i) applying a catalytic liquid suspension to a surface of a scaffold to provide a coating comprising catalytically reactive sites on the surface of the scaffold, where the catalytic liquid suspension comprises a liquid carrier comprising a plurality of catalyst particles less than about 5 μm. In an embodiment, the scaffold may be a static mixer. In an embodiment or example, the surface of the static mixer may be pre-coated with a support material and optionally a binder prior to step (i). In an example, the catalytic liquid suspension further comprises a binder. In an embodiment, applying the catalytic liquid suspension to the surface of the scaffold in step (i) may be by wash coating or dip coating.
[0043] In another embodiment or example, a process for coating a static mixer scaffold may include the steps of: (i) applying a catalytic liquid suspension to a surface of the scaffold, where the catalytic liquid suspension comprises catalyst particles having a particle size of less than about 5 μm and a liquid carrier, to provide catalytic reactive sites on the surface of the scaffold, the static mixer surface being (a) a static mixer scaffold, (b) a static mixer scaffold comprising a support material, or (c) a static mixer scaffold comprising a support material and a binder. The catalytic liquid suspension may further comprise a binder.
[0044] In one embodiment or example, the step of applying the catalytic liquid suspension to the surface of the scaffold in step (i) can be wash-coating or dip-coating. The inventors have surprisingly shown that wash-coating or dip-coating deposition techniques provide advantages to catalytic static mixers, such as an effective and scalable method for deposition of catalytic materials onto the static mixer scaffold, for example, by wash-coating / dip-coating the static mixer in the catalytic liquid suspension. This technique may include the incorporation of binding materials to promote better adhesion or improve specific functions, via the addition of Teflon to increase hydrophobicity, with the advantage of a small diffusion distance to the active phase. It will be appreciated that standard catalytic coating techniques typically involve a two-step process, first forming a porous metal oxide layer, and then second impregnating the catalyst into the pre-formed porous layer. Other coating techniques, such as electrodeposition and cold spray techniques, are limited by the type of metal that can be coated, and the size of the metal to be coated. Other limitations include line-of-sight configurations, which impose constraints on the coating technique. For example, line-of-sight coating techniques generally allow for coverage of the exposed areas of the scaffold surface, i.e., the twisted plate configuration. Several methods have been reported for depositing coatings onto various scaffolds. Cold spray techniques are frequently used, but because only the exposed surface of the scaffold can be coated, the coverage of the coating is incomplete and uneven, with some areas remaining uncovered.
[0045] It should be appreciated that the inventors have shown that the wash-coating or dip-coating deposition technique as described herein provides more complete coverage of even complex scaffold configurations. In other words, the wash-coating or dip-coating deposition technique is a non-line-of-sight coating technique that can provide more complete coverage of the surface of the scaffold. For example, a scaffold with a complex geometry having shadowed areas can be referred to as a non-line-of-sight configuration or a non-line-of-sight scaffold.
[0046] In certain embodiments or examples, the process may comprise a pre-treatment step prior to applying the liquid suspension to the surface of the scaffold in step (i), which pre-treatment step may be at least one surface treatment step selected from chemical treatment, anodizing, hot dip plating, vacuum plating, painting, thermal spraying, and acid etching.
[0047] In some embodiments, chemical treatment may include processes that create thin films of sulfides and oxides through chemical reactions. Typical applications are metal coloring, corrosion prevention, and priming for painted surfaces. Black oxide is a very common surface treatment for steel parts, and "passivation" is used to remove free iron from the surface of stainless steel parts.
[0048] In another example, anodizing may be used on light metals, typically aluminum and titanium. These oxide coatings are formed by electrolysis, and because they are porous, stains and colorants are often specified to improve the aesthetic appearance. Anodizing is a very common surface treatment that protects aluminum parts from corrosion. When wear resistance is also desired, engineers may specify a version of this method that forms a relatively thick, very hard ceramic coating on the surface of the part.
[0049] In another example, hot dip galvanizing may require dipping the scaffolding into molten tin, lead, zinc, aluminum, or solder to form a metallic film on the surface. Hot dip galvanizing is a process in which steel is immersed in a vessel containing molten zinc and is typically used for corrosion resistance in extreme environments; road guardrails are commonly treated with this surface treatment.
[0050] In another example, vacuum plating may be used. Vacuum deposition, sputtering, ion plating, ion nitriding, and ion implantation are typical metal surface finishing processes that utilize high vacuum as part of the plating process. Ionized metals, oxides, and nitrides are created in a controlled environment. The part is transferred to a vacuum chamber and the metal is deposited very precisely on the substrate. Titanium nitride is a surface treatment that extends the life of high steel and hard metal cutting tools.
[0051] In another example, it is common for engineers to specify painting to enhance the appearance and corrosion resistance of scaffolding. Spray painting, electrostatic painting, dipping, brushing, and powder coating methods are some of the most common techniques used to apply paint to the surface of components. There are many types of paint formulations to protect metal parts in a wide range of physical environments. The automotive industry has automated the painting process for cars and trucks, utilizing thousands of robotic arms to produce extremely consistent results.
[0052] In another example, thermal spraying is a type of surface treatment that involves molten or heated material being accelerated and then impacting to mechanically bond to a target surface. A wire or powder feedstock (usually metal or ceramic) is melted by injecting it into a flame, electric arc, or plasma stream. Engineers may specify this process when additional friction is a desired property. This technique is also commonly used on larger structures for protection against high temperatures, such as thermal barrier coatings for exhaust heat management.
[0053] In another example, acid etching involves cutting hard surfaces such as metal or glass with a caustic chemical, usually an acid. A typical application is etching dental enamel with acid to roughen the surface, enhance retention of resin sealants, and promote mechanical retention.
[0054] It will be appreciated that there are many other unique surface treatments and variations of the most common processes that are designed to improve or modify the properties of metal parts.
[0055] In one embodiment or example, the catalyst particles are formed from a catalyst material or a catalyst support material that includes a catalyst material on a support material. In some embodiments or examples, the catalyst particles can be in the range of 0.1 nm to 10 mm, 1 nm to 5 mm, 100 nm to 1 mm, 1 μm to 200 μm, 0.25 μm to 50 μm, or 0.5 μm to 5 μm. The catalyst particles can be less than 5 mm, 1 mm, 100 μm, 10 μm, 5 μm, 1 μm, 500 nm, 250 nm, 100 nm, or 50 nm. The catalyst particles can be at least 0.1 nm, 1 nm, 10 nm, 100 nm, 250 nm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, or 50 μm. The catalyst particles can be in the range provided by any two of these upper and / or lower limits. It is understood that the size of the catalyst particles is controlled by dry or wet milling as needed. For example, the catalyst particles are less than 5 μm. It is also understood that the catalyst particles formed from the catalyst material or catalyst support material are controlled by dry or wet milling as needed. For example, the catalyst material or catalyst support material is less than 5 μm. In some embodiments or examples, the catalyst particles may be in the form of spheres, pellets, cylinders, trilobes, honeycombs, plates, and quadralobates.
[0056] In another embodiment or example, the catalyst particles may be ex-situ catalyst particles. For example, ex-situ catalysts may include catalysts that are prepared such that the catalyst particles are in their final form before being deposited on the surface of the scaffold. Catalyst particles in a catalytic solution may be considered to be ex-situ if they have at least some catalytic activity, regardless of an activation reaction such as calcination. It will be understood that ex-situ catalysts may differ from in-situ catalysts. An in-situ catalyst may be a catalyst precursor that is applied to the surface of the scaffold, which requires a further processing step to generate an active catalyst in its final form, for example, via activation such as calcination.
[0057] In another embodiment or example, the catalytic material can be selected from a metal, a metal oxide, an aluminum silicate, an activated carbon, a mesoporous carbon, a graphene, a graphitic material, a metal organic framework, a zeolite, or any combination thereof. The catalytic material may be a metal, a metal oxide, or a zeolite. In an example, the metal is selected from at least one of aluminum, iron, calcium, magnesium, cerium, cobalt, copper, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or metal oxides thereof.
[0058] In another embodiment or example, the support material may be selected from at least one of activated carbon, mesoporous carbon, graphene, graphite materials, metal organic frameworks, zeolites, aluminum oxide, silicon dioxide, ceramics, magnesium chloride, calcium carbonate, or dipotassium oxide. The support material may be aluminum oxide, activated carbon, silica, zeolites, or calcium carbonate.
[0059] In another embodiment or example, the catalyst support material can be selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel-modified aluminum oxide, silicon oxide, or zeolite. The catalyst support material can be silica diphenylphosphine palladium, zeolite, activated carbon, palladium on titanium silicate, lead-poisoned palladium on calcium carbonate, nickel-modified aluminum oxide, silicon oxide, or ruthenium on aluminum oxide.
[0060] The catalytic liquid suspension may include a catalytic material or a catalytic support material. The catalytic particles may be formed from the catalytic material or the catalytic support material. The catalytic support material provides the catalytic material present with a support material. For example, the catalytic support material may include a catalytic particle including catalytic material particles present with or on a support material particle. It will be understood that when a catalytic material is used as a support material, the catalytic material and the support material will be different. In one embodiment, the support material may be provided as a major component of the catalytic particle, such as when the size of the support material particles is substantially larger than the catalytic material particles present on the surface of the support material particles.
[0061] In some embodiments or examples, the concentration of catalytic material in the catalytic liquid suspension may be less than 20%, 15%, 10%, 8%, 6%, 5%, 4%, 3%, or 2% by weight. The concentration of catalytic material in the catalytic liquid suspension may be at least 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, or 15% by weight. The concentration of catalytic material in the catalytic liquid suspension may be in the range of 1-20%, 2-15%, 3-10%, 4-8%, or 5-6% by weight. The concentration of catalytic material may be in the range provided by any two of these upper and / or lower limits.
[0062] The weight percent of the coating or catalytic material based on the total weight of the catalytic static mixer can be in the range of 1-40%, 2-35%, 5-30%, 10-25%, or 15-20%. The weight percent of the coating that includes catalytic material based on the total weight of the catalytic static mixer can be at least 1%, 5%, 10%, 15%, 20%, 35%, 30%, 35%, or 40%. The weight percent of the coating that includes catalytic material based on the total weight of the catalytic static mixer can be less than 50%, 40%, 30%, 20%, 15%, 10%, 5%, or 3%. The weight percent of the coating that includes catalytic material can be in the range provided by any two of these upper and / or lower limits.
[0063] In some embodiments or examples, the binder may be selected from the group including hydroxypropyl cellulose, methyl cellulose, polyester, polyurethane, acrylic resin, condensation resin, polyvinyl acetate, poly(acrylic acid) sodium salt, polyvinylidene fluoride, polyethylene oxide, polyethylene glycol, dextrin, sodium silicate, colloidal silica, polydimethylsiloxane, boehmite, colloidal aluminum oxide, or polyisobutylene. The binder may be hydroxypropyl cellulose, sucrose, dextrin, or starch. The binder may be hydroxypropyl cellulose, polyvinyl acetate, polyethylene glycol, sodium silicate, or colloidal silica. The binder may be hydroxypropyl cellulose, polyvinyl acetate, or colloidal silica. The binder may be hydroxypropyl cellulose, polyvinyl acetate, or polydimethylsiloxane. The binder may be boehmite or colloidal aluminum oxide.
[0064] In some embodiments or examples, the binder may be added at a concentration between about 0.3% and about 5% by weight. The concentration of the binder in the catalytic liquid suspension may be within the range of 0.1% to 10% by weight, 0.2% to 8% by weight, 0.3% to 6% by weight, 0.4% to 5% by weight, or 0.5% to 3% by weight. The concentration of the binder in the catalytic liquid suspension may be less than about 10%, 8%, 6%, 4%, 3%, 2%, 1%, 0.9%, 0.8%, 0.6%, 0.4%, 0.2%, or 0.1% by weight. The concentration of the binder in the catalytic liquid suspension may be at least about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% by weight. The concentration of the binder in the catalytic liquid suspension may be in a range provided by any two of these upper and / or lower limits.
[0065] In some embodiments or examples, the liquid carrier may be selected from the group including water, ethanol, isopropanol, butanol, ethyl acetate, acetone, or a combination thereof. For example, the solvent may be selected from water or ethanol. The solvent may be water. The solvent may be ethanol.
[0066] In some embodiments or examples, the liquid suspension may have a solids content between about 3% and about 28% by weight. The solids content may be less than 28%, 27%, 25%, 23%, 21%, 19%, 17%, 15%, 13%, 11%, 9%, 7%, 5%, or 3% by weight. The solids content may be at least 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, or 26% by weight. The solids content may be within a range provided by any two of these upper and / or lower limits.
[0067] In some embodiments or examples, the coating thickness is between about 1 μm and about 50 μm. The coating thickness may be in the range of 1-40%, 2-35%, 5-30%, 10-25%, or 15-20%. The coating thickness may be at least 1%, 5%, 10%, 15%, 20%, 35%, 30%, 35%, or 40%. The coating thickness may be less than 50%, 40%, 30%, 20%, 15%, 10%, 5%, or 3%. The coating thickness may be within the range provided by any two of these upper and / or lower limits.
[0068] In some embodiments or examples, the catalyst has a surface area of about 1 m 2 / g~about 1000m 2 The surface area of the catalyst is at least 1, 5, 50, 100, 150, 200, 250, 300, 350, 400, 550, 600, 650, 700, 750, 800, 850, 900, 950 m 2 The surface area of the catalyst can be about 5 to 200 m 2 / g, 100-250m 2 / g, 150-1000m 2 / g, or 200-800m 2 The surface area of the catalyst can be in the range provided by any two of these upper and / or lower limits.
[0069] It will be understood that the total mass loss of the coating may relate to the integrity of the coating's adhesion. It will be understood that the adhesion of the coating may be determined via the mass loss from the sonication test. The inventors have surprisingly found that the process for coating the static mixer scaffold as described herein advantageously results in a catalytic static mixer scaffold with enhanced or improved coating adhesion. In some embodiments or examples, the total mass loss of the coating may be less than about 5 wt.%. The total mass loss of the coating may be less than about 5 wt.%, 4 wt.%, 3 wt.%, 2 wt.%, 1 wt.%, 0.8 wt.%, 0.6 wt.%, 0.4 wt.%, 0.2 wt.%, or 0.1 wt. In some embodiments or examples, the total mass loss of the coating may be less than about 0.5 wt. The total mass loss of the coating may be less than about 1 wt.%, 0.8 wt.%, 0.6 wt.%, 0.4 wt.%, 0.2 wt.%, or 0.1 wt.%. It will be appreciated that adhesion is an important quality of a coating since it allows the coating to perform its function of protecting or decorating the substrate. It will be appreciated that various adhesion test methods can be applied to determine the adhesion strength of the coating on the scaffold as the force required to break the bond between the coating and the scaffold under given conditions. For example, two different test methods are covered in ASTM D3359-17 or ASTM D6677. The inventors have surprisingly found that the enhanced or improved coating adhesion prepared by the process described herein advantageously results in active catalytic metals on the catalytically active static mixer scaffold, which can be used continuously for extended periods of time with negligible degradation of the active catalytic metals. In certain embodiments or examples, the total leaching rate of the active catalytic metals under standard operating conditions can be less than 350 parts per billion (ppb) of contamination in the reactor effluent. The total leaching rate may be less than about 400, 350, 300, 250, 200, 150, 100, 70, 40, 10, 5, 1, or 0.5 (ppb).
[0070] The catalytic liquid suspension may comprise or consist of a catalytic material or a catalytic support material. The catalytic liquid suspension may comprise or consist of catalyst particles and a binder. The catalytic liquid suspension may comprise or consist of a catalytic material, a support material, a binder, and a liquid carrier. The catalytic liquid suspension may comprise or consist of a catalytic material, a binder, and a liquid carrier. The catalytic liquid suspension may comprise or consist of a catalytic support material, a binder, and a liquid carrier. The catalytic liquid suspension may comprise or consist of a catalytic support material, a binder, and a liquid carrier. The catalytic liquid suspension may comprise or consist of a catalytic material and a liquid carrier. The catalytic liquid suspension may comprise or consist of a catalytic support material and a liquid carrier. The catalytic liquid suspension may comprise or consist of a catalytic support material and a liquid carrier. The catalytic liquid suspension may comprise or consist of a catalytic support material and a liquid carrier. The catalytic liquid suspension may comprise or consist of a catalytic support material, a support material, and a liquid carrier.
[0071] Option (a) In an embodiment or example, a process for preparing a catalytically coated scaffold is provided, which includes the steps of: (i) applying a catalytic liquid suspension to a surface of a scaffold to provide a coating comprising catalytically reactive sites on the surface of the scaffold, where the catalytic liquid suspension comprises a liquid carrier comprising a plurality of catalytic particles less than about 5 μm. For example, the surface of the scaffold is a static mixer. The catalytic liquid suspension comprising a liquid carrier comprising a plurality of catalytic particles less than about 5 μm may comprise or consist of a catalytic material or a catalytic support material. The catalytic liquid suspension may comprise or consist of a catalytic material and a catalytic support material. The catalytic liquid suspension may comprise or consist of a catalytic material. The catalytic liquid suspension may comprise or consist of a catalytic support material. The catalytic liquid suspension may comprise or consist of a catalytic material and a catalytic support material. The catalytic liquid suspension may comprise or consist of a catalytic material and a catalytic support material. The catalytic liquid suspension may comprise or consist of a catalytic material and a catalytic support material. The catalytic liquid suspension may comprise or consist of a catalytic material and a catalytic support material. The catalytic liquid suspension may comprise or consist of a catalytic material and a catalytic support material. The catalytic liquid suspension may comprise or consist of a catalyst support material and a liquid carrier.
[0072] In another embodiment or example, the catalytic material may be selected from a metal, a metal oxide, an aluminum silicate, an activated carbon, a mesoporous carbon, a graphene, a graphite material, a metal organic framework, a zeolite, or any combination thereof. The catalytic material may be a metal, a metal oxide, or a zeolite. In an example, the metal is selected from at least one of aluminum, iron, calcium, magnesium, cerium, cobalt, copper, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or metal oxides thereof. In an embodiment or example, the catalytic support material may be selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel-modified aluminum oxide, silicon oxide, or a zeolite. The catalyst support material may be silica diphenylphosphine palladium, zeolite, activated carbon, palladium on titanium silicate, lead poisoned palladium on calcium carbonate, nickel modified aluminum oxide silicon oxide, or ruthenium on aluminum oxide. In some embodiments or examples, the catalyst material or catalyst support material may be activated carbon, ruthenium on aluminum oxide, palladium on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, mesoporous carbon, zeolite, or nickel modified aluminum oxide silicon oxide. The catalyst material may be ruthenium on aluminum oxide, palladium on aluminum oxide, silver on aluminum oxide, or iron on aluminum oxide. The catalyst support material may be ruthenium on aluminum oxide or palladium on aluminum oxide. In some embodiments or examples, the liquid support may be ethanol or water. In some examples, the catalyst support material may be ruthenium on aluminum oxide and the liquid support may be water.In another embodiment, the catalyst support material may be palladium on aluminum oxide and the liquid carrier may be water. In another embodiment, the catalyst support material may be silver on aluminum oxide and the liquid carrier may be water. In another embodiment, the catalyst support material may be iron on aluminum oxide and the liquid carrier may be water. In an embodiment, the catalyst support material may be ruthenium on aluminum oxide and the liquid carrier may be ethanol. In another embodiment, the catalyst support material may be palladium on aluminum oxide and the liquid carrier may be ethanol. In another embodiment, the catalyst support material may be silver on aluminum oxide and the liquid carrier may be ethanol. In another embodiment, the catalyst support material may be iron on aluminum oxide and the liquid carrier may be ethanol.
[0073] Option (b) In one embodiment or example, a process for preparing a catalytically coated scaffold is provided, comprising the steps of: (i) applying a catalytic liquid suspension to a surface of a scaffold to provide a coating comprising catalytically reactive sites on the surface of the scaffold, wherein the catalytic liquid suspension comprises a liquid carrier comprising a plurality of catalyst particles less than about 5 μm, for example, the surface of the scaffold is a static mixer comprising a support material.
[0074] The catalytic liquid suspension, which includes a liquid carrier containing a plurality of catalyst particles less than about 5 μm, may include or consist of a catalytic material and a support material. The catalytic liquid suspension may include or consist of a catalytic support material and a support material. The catalytic liquid suspension may include or consist of a catalytic support material, a support material, and a liquid carrier. The catalytic liquid suspension may include or consist of a catalytic material, a support material, and a liquid carrier.
[0075] In another embodiment or example, the catalytic material may be selected from a metal, a metal oxide, an aluminum silicate, an activated carbon, a mesoporous carbon, a graphene, a graphitic material, a metal organic framework, a zeolite, or any combination thereof. The catalytic material may be a metal, a metal oxide, or a zeolite. In an example, the metal is selected from at least one of aluminum, iron, calcium, magnesium, cerium, cobalt, copper, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or a metal oxide thereof. For example, the metal oxide may be an iron oxide, a cerium oxide, a manganese oxide, a vanadium oxide, or a cobalt oxide. In another embodiment or example, the catalyst support material may be selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel-modified aluminum oxide, silicon oxide, or zeolite. The catalyst support material may be silica diphenylphosphine palladium, zeolite, activated carbon, palladium on titanium silicate, lead-poisoned palladium on calcium carbonate, nickel-modified aluminum oxide, silicon oxide, or ruthenium on aluminum oxide. The catalyst support material may be silica diphenylphosphine palladium, zeolite, mesoporous carbon, palladium on titanium silicate, lead-poisoned palladium on calcium carbonate, nickel-modified aluminum oxide, silicon oxide, or ruthenium on aluminum oxide. In an embodiment or example, the catalyst material or catalyst support material may be silica diphenylphosphine palladium or zeolite. In certain embodiments or examples, the support material may be selected from at least one of activated carbon, mesoporous carbon, graphene, graphitic materials, metal organic frameworks, zeolites, aluminum oxide, silicon dioxide, ceramics, magnesium chloride, calcium carbonate, or dipotassium oxide.The support material may be aluminum oxide, activated carbon, silica, zeolite, or calcium carbonate. In some embodiments or examples, the support material may be aluminum oxide. In some embodiments or examples, the liquid carrier may be ethanol or water. In some examples, the catalyst support material may be silica diphenylphosphine palladium, the support material may be aluminum oxide, and the liquid carrier may be ethanol. In some examples, the catalyst support material may be silica diphenylphosphine palladium, the support material may be aluminum oxide, and the liquid carrier may be water. In another example, the catalyst material may be selected from iron oxide, cerium oxide, manganese oxide, vanadium oxide, or cobalt oxide, the support material may be aluminum oxide, and the liquid carrier may be water or ethanol. In another example, the catalyst material may be iron oxide, the support material may be aluminum oxide, and the liquid carrier may be water. In another example, the catalyst material may be iron oxide, the support material may be aluminum oxide, and the liquid carrier may be ethanol. In another embodiment, the catalytic material may be cerium oxide, the support material may be aluminum oxide, and the liquid carrier may be water. In another embodiment, the catalytic material may be cerium oxide, the support material may be aluminum oxide, and the liquid carrier may be ethanol. In another embodiment, the catalytic material may be manganese oxide, the support material may be aluminum oxide, and the liquid carrier may be water. In another embodiment, the catalytic material may be manganese oxide, the support material may be aluminum oxide, and the liquid carrier may be ethanol. In another embodiment, the catalytic material may be vanadium oxide, the support material may be aluminum oxide, and the liquid carrier may be water. In another embodiment, the catalytic material may be vanadium oxide, the support material may be aluminum oxide, and the liquid carrier may be ethanol.In another embodiment, the catalytic material may be cobalt oxide, the support material may be aluminum oxide, and the liquid carrier may be ethanol. In another embodiment, the catalytic material may be cobalt oxide, the support material may be aluminum oxide, and the liquid carrier may be water.
[0076] Option (c) In one embodiment or example, a process for preparing a catalytically coated scaffold is provided, comprising the steps of: (i) applying a catalytic liquid suspension to a surface of a scaffold to provide a coating comprising catalytically reactive sites on the surface of the scaffold, where the catalytic liquid suspension comprises a liquid carrier comprising a plurality of catalyst particles less than about 5 μm, for example, a static mixer comprising a support material and a binder.
[0077] A catalytic liquid suspension comprising a liquid carrier containing a plurality of catalyst particles less than about 5 μm may comprise or consist of a catalyst material, a support material, a binder, and a liquid carrier. The catalytic liquid suspension may comprise or consist of a catalyst support material, a support material, a binder, and a liquid carrier.
[0078] In another embodiment or example, the catalytic material may be selected from a metal, a metal oxide, an aluminum silicate, an activated carbon, a mesoporous carbon, a graphene, a graphite material, a metal organic framework, a zeolite, or any combination thereof. The catalytic material may be a metal, a metal oxide, or a zeolite. In an example, the metal is selected from at least one of aluminum, iron, calcium, magnesium, cerium, cobalt, copper, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or metal oxides thereof. In another embodiment or example, the catalytic support material may be selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel-modified aluminum oxide, silicon oxide, or a zeolite. The catalyst support material may be silica diphenylphosphine palladium, zeolite, activated carbon, palladium on titanium silicate, lead poisoned palladium on calcium carbonate, nickel modified aluminum oxide silicon oxide, or ruthenium on aluminum oxide. In some embodiments or examples, the catalyst material or catalyst support material may be a zeolite or activated carbon. In other embodiments or examples, the catalyst support material may be a zeolite. In some embodiments or examples, the support material may be selected from at least one of activated carbon, mesoporous carbon, graphene, graphite material, metal organic framework, zeolite, aluminum oxide, silicon dioxide, ceramic, magnesium chloride, calcium carbonate, or dipotassium oxide. The support material may be aluminum oxide, activated carbon, silica, zeolite, or calcium carbonate. The support material may be aluminum oxide.In some embodiments or examples, the binder may be selected from the group including hydroxypropyl cellulose, methyl cellulose, polyester, polyurethane, acrylic resin, condensation resin, polyvinyl acetate, poly(acrylic acid) sodium salt, polyvinylidene fluoride, polyethylene oxide, polyethylene glycol, dextrin, sodium silicate, colloidal silica, polydimethylsiloxane, boehmite, colloidal aluminum oxide, or polyisobutylene. The binder may be hydroxypropyl cellulose, sucrose, dextrin, or starch. The binder may be hydroxypropyl cellulose, polyvinyl acetate, polyethylene glycol, sodium silicate, or colloidal silica. The binder may be hydroxypropyl cellulose, polyvinyl acetate, or colloidal silica. The binder may be hydroxypropyl cellulose, polyvinyl acetate, or polydimethylsiloxane. The binder may be boehmite or colloidal aluminum oxide. The binder may be hydroxypropyl cellulose or colloidal silica. In some embodiments or examples, the binder may be hydroxypropyl cellulose. In some embodiments or examples, the liquid carrier may be ethanol or water. In some examples, the catalytic material may be zeolite, the support material may be aluminum oxide, the binder may be hydroxypropyl cellulose, and the liquid carrier may be water. In some examples, the catalytic material may be zeolite, the support material may be aluminum oxide, the binder may be hydroxypropyl cellulose, and the liquid carrier may be ethanol. In some examples, the catalytic material may be zeolite, the support material may be aluminum oxide, the binder may be hydroxypropyl cellulose, and the liquid carrier may be ethanol. In some examples, the catalytic material may be zeolite, the support material may be aluminum oxide, the binder may be colloidal silica, and the liquid carrier may be ethanol.In some embodiments, the catalytic material may be a zeolite, the support material may be aluminum oxide, the binder may be colloidal silica, and the liquid carrier may be water. In some embodiments, the catalytic material may be activated carbon, the support material may be aluminum oxide, the binder may be colloidal silica, and the liquid carrier may be water. In some embodiments, the catalytic material may be activated carbon, the support material may be aluminum oxide, the binder may be colloidal silica, and the liquid carrier may be ethanol. In some embodiments, the catalytic material may be activated carbon, the support material may be aluminum oxide, the binder may be hydroxypropyl cellulose, and the liquid carrier may be ethanol. In some embodiments, the catalytic material may be activated carbon, the support material may be aluminum oxide, the binder may be hydroxypropyl cellulose, and the liquid carrier may be water.
[0079] Option (d) In one embodiment or example, a process for preparing a catalytically coated scaffold is provided, comprising the steps of: (i) applying a catalytic liquid suspension to a surface of a scaffold to provide a coating comprising catalytically reactive sites on the surface of the scaffold, wherein the catalytic liquid suspension comprises a liquid carrier comprising a plurality of catalyst particles less than about 5 μm, for example, the surface of the scaffold is a static mixer in which the catalytic liquid suspension comprises a liquid carrier comprising a plurality of catalyst particles less than about 5 μm and a binder.
[0080] The catalytic liquid suspension, which includes a liquid carrier that includes a plurality of catalyst particles less than about 5 μm, may include or consist of a catalyst material, a binder, and a liquid carrier. The catalytic liquid suspension may include or consist of a catalyst support material, a binder, and a liquid carrier.
[0081] In another embodiment or example, the catalytic material may be selected from a metal, a metal oxide, an aluminum silicate, an activated carbon, a mesoporous carbon, a graphene, a graphite material, a metal organic framework, a zeolite, or any combination thereof. The catalytic material may be a metal, a metal oxide, or a zeolite. In an example, the metal may be selected from at least one of aluminum, iron, calcium, magnesium, cerium, cobalt, copper, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or metal oxides thereof. In another embodiment or example, the catalytic support material may be selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel-modified aluminum oxide, silicon oxide, or a zeolite. The catalyst support material may be silica diphenylphosphine palladium, zeolite, activated carbon, palladium on titanium silicate, lead poisoned palladium on calcium carbonate, nickel modified aluminum oxide, silicon oxide, or ruthenium on aluminum oxide. In some embodiments or examples, the binder may be selected from the group including hydroxypropyl cellulose, methyl cellulose, polyester, polyurethane, acrylic resin, condensation resin, polyvinyl acetate, poly(acrylic acid) sodium salt, polyvinylidene fluoride, polyethylene oxide, polyethylene glycol, dextrin, sodium silicate, colloidal silica, polydimethylsiloxane, boehmite, colloidal aluminum oxide, or polyisobutylene. The binder may be hydroxypropyl cellulose, sucrose, dextrin, or starch. The binder may be hydroxypropyl cellulose, polyvinyl acetate, polyethylene glycol, sodium silicate, or colloidal silica. The binder may be hydroxypropyl cellulose, polyvinyl acetate, or colloidal silica.The binder may be hydroxypropyl cellulose, polyvinyl acetate, or polydimethylsiloxane. The binder may be boehmite or colloidal aluminum oxide. The binder may be hydroxypropyl cellulose. The binder may be hydroxypropyl cellulose, colloidal silica, polyvinylidene fluoride, poly(acrylic acid) sodium salt, or polyvinyl acetate. In some embodiments or examples, the liquid carrier may be ethanol or water. In some embodiments or examples, the catalyst support material may be silica diphenylphosphine palladium, lead poisoned palladium on calcium carbonate, palladium on titanium silicate, nickel modified aluminum oxide silicon oxide, mesoporous carbon, or zeolite, the binder may be hydroxypropyl silica or colloidal silica, and the liquid carrier may be ethanol or water. In some embodiments, the catalyst support material may be ruthenium on aluminum, the binder may be hydroxypropyl cellulose, and the liquid carrier may be ethanol. In another embodiment, the catalyst support material may be lead-poisoned palladium on calcium carbonate, the binder may be hydroxypropyl cellulose, and the liquid carrier may be ethanol. In another embodiment, the catalyst support material may be palladium on titanium silicate, the binder may be hydroxypropyl cellulose, and the liquid carrier may be ethanol. In another embodiment, the catalyst support material may be palladium on titanium silicate, the binder may be hydroxypropyl cellulose, and the liquid carrier may be water. In another embodiment, the catalyst support material may be nickel-modified aluminum oxide, the binder may be hydroxypropyl cellulose, and the liquid carrier may be ethanol. In another embodiment, the catalyst material may be mesoporous carbon, the binder may be hydroxypropyl cellulose, and the liquid carrier may be ethanol. In another embodiment, the catalyst material may be zeolite, the binder material may be hydroxypropyl cellulose, and the liquid carrier may be water.In another embodiment, the catalyst material may be a zeolite, the binder may be a silicon oxide, and the liquid carrier may be water. In an embodiment, the catalyst material may be a zeolite, the binder material may be hydroxypropyl cellulose and silicic acid oxide, and the liquid carrier may be water. In an embodiment, the catalyst support material may be ruthenium on aluminum, the binder may be colloidal silica, and the liquid carrier may be ethanol. In another embodiment, the catalyst support material may be lead-poisoned palladium on calcium carbonate, the binder may be colloidal silica, and the liquid carrier may be ethanol. In another embodiment, the catalyst support material may be palladium on titanium silicate, the binder may be colloidal silica, and the liquid carrier may be ethanol. In another embodiment, the catalyst support material may be palladium on titanium silicate, the binder may be colloidal silica, and the liquid carrier may be water. In another embodiment, the catalyst support material may be nickel-modified aluminum oxide silicon oxide, the binder may be colloidal silica, and the liquid carrier may be ethanol. In another embodiment, the catalytic material may be mesoporous carbon, the binder may be colloidal silica, and the liquid carrier may be ethanol. In another embodiment, the catalytic material may be zeolite, the binder material may be colloidal silica, and the liquid carrier may be water. In another embodiment, the catalytic material may be zeolite, the binder material may be colloidal silica, and the liquid carrier may be water. In another embodiment, the catalytic material may be zeolite, the binder material may be colloidal silica, and the liquid carrier may be water. In another embodiment, the catalytic material may be zeolite, the binder material may be colloidal silica, and the liquid carrier may be water. In another embodiment, the catalytic material may be calcium oxide, the binder may be hydroxypropyl cellulose, and the liquid carrier may be ethanol. In another embodiment, the catalytic material may be magnesium oxide, the binder may be hydroxypropyl cellulose, and the liquid carrier may be ethanol.
[0082] scaffold In some embodiments or examples, the scaffold may be applied to any device or apparatus. In another embodiment or example, the scaffold may be a complex 3D structure. The complex 3D structure may be porous. In some embodiments or examples, the scaffold may be suitable for continuous flow processes. The processes described herein may be suitable for coating the inner surface of a continuous flow reactor. In some embodiments or examples, the scaffold may be a rotary mixer, a continuous pipe, a micromixer, a static mixer, an integral porous insert, a metal foam, a structured metal or ceramic material (with voids such as honeycomb), a metal mesh / plate, a mold structure, or a packed bed system. In some embodiments or examples, the scaffold may be a static mixer.
[0083] The scaffold of the static mixer may include or consist of at least one of a metal, a metal alloy, a cermet, silicon carbide, a glass, a ceramic, a mineral (e.g., calcium phosphate), or a polymer. The scaffold may be, for example, a metallic scaffold formed from a metal or a metal alloy. The metallic scaffold may be prepared from a material suitable for additive manufacturing (i.e., 3D printing). The metallic scaffold may be prepared from a material suitable for further surface modification to provide or enhance catalytic reactivity, for example, a metal including nickel, titanium, palladium, platinum, gold, copper, aluminum or alloys thereof, for example, metal alloys such as stainless steel. In one embodiment, the metal for the scaffold may include or consist of titanium, stainless steel, and alloys of cobalt and chromium. In another embodiment, the metal for the scaffold may include or consist of titanium, aluminum, or stainless steel. In another embodiment, the metal for the scaffold may include or consist of stainless steel and cobalt chromium alloys. Using additive manufacturing technology, i.e., 3D metal printing, metal scaffolds can be specially designed to perform two main tasks: a) to act as a substrate for the catalyst layer or catalyst layers, and b) to act as a flow guide for optimal mixing performance during chemical reactions and then to assist in the transfer of heat to the walls of the reaction tube inside the reactor (single-phase liquid flow or multi-phase flow). Alternatively, the scaffold may be made from carbon fiber. Alternatively, the scaffold may be made from glass. Alternatively, the scaffold may be made from ceramic. Alternatively, the scaffold may be made from minerals (e.g., calcium phosphates such as hydroxyapatite). Alternatively, the scaffold may be made from a polymer. The polymer may be thermosetting or thermoplastic. Examples of polymers that may be used include, but are not limited to, polycarbonate, polymethylmethacrylate, polypropylene, polyethylene, polyamide, polyacrylamide, polyvinyl chloride, or copolymers, or any combination thereof.
[0084] A catalyst material or catalyst support material may refer to a catalyst by itself or to a material or composition that includes a catalyst. The catalyst material or catalyst support material may be provided in a composition that includes one or more additives, such as binders, to facilitate coating of the catalyst onto the scaffold. The catalyst or coating may be provided as a partial coating or a complete layer on the scaffold. The catalyst coating or layer on the scaffold may be provided in one or more layers. The catalyst may be deposited on the scaffold by wash coating or dip coating. In some embodiments or examples, the catalyst coating or layer may be a plurality of catalyst layers. For example, the catalyst coating or layer may be one of a plurality of layers. The catalyst coating or layer may be 2-10 layers. The catalyst coating or layer may be at least 2, 3, 4, 5, 6, 7, or 8 layers. The catalyst coating or layer may be less than 8, 7, 6, 5, 4, 3, or 2 layers. The catalyst coating or layer may be in a range provided by any two of these upper and / or lower limits.
[0085] In an embodiment or example, the catalyst loading may be less than 20%, 18%, 16%, 14%, 12%, 10%, 8%, 6%, 4%, or 2% by weight. The catalyst loading may be at least 1%, 3%, 5%, 7%, 9%, 11%, 13%, 15%, 17%, or 19% by weight. The catalyst loading may be in a range provided by any two of these upper and / or lower limits.
[0086] In one embodiment, the scaffold may be a metal scaffold comprising a coating comprising a catalytic material. It will be understood that a metal scaffold comprising a coating comprising a catalytic material may be referred to as a catalytically coated scaffold. In another embodiment, the metal scaffold comprises titanium, nickel, aluminum, stainless steel, cobalt, chromium, any alloy thereof, or any combination thereof. In another embodiment, the metal scaffold comprises at least one of stainless steel and aluminum. In another embodiment, the metal scaffold comprises titanium, or a titanium alloy. Further advantages may be provided when the metal scaffold comprises or consists of stainless steel or a cobalt chromium alloy.
[0087] The weight percent of the coating or catalytic material, based on the total weight of the catalytic static mixer, can be in the range of 1-40%, 2-35%, 5-30%, 10-25%, or 15-20%. The weight percent of the coating including catalytic material, based on the total weight of the catalytic static mixer, can be at least 1%, 5%, 10%, 15%, 20%, 35%, 30%, 35%, or 40%. The weight percent of the coating including catalytic material, based on the total weight of the catalytic static mixer, can be less than 50%, 40%, 30%, 20%, 15%, 10%, 5%, or 3%. The weight percent of the coating or catalytic material, based on the total weight of the catalytic static mixer, can be in the range provided by any two of these upper and / or lower limits.
[0088] In some embodiments or examples, the catalytically coated scaffold, including the coating on the scaffold, may include a coating comprising a plurality of catalytic particles. In some embodiments or examples, the coating comprises a support material and optionally a binder. The catalytic particles may be selected from metals, metal oxides, aluminum silicate, activated carbon, mesoporous carbon, graphene, graphitic materials, metal organic frameworks, zeolites, or any combination thereof.
[0089] In some embodiments or examples, the catalyst particles can be a metal selected from at least one of aminium, iron, cerium, calcium, cobalt, copper, magnesium, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or a metal oxide thereof.
[0090] In certain embodiments or examples, the support material may be selected from at least one of activated carbon, mesoporous carbon, graphene, graphitic materials, metal organic frameworks, zeolites, aluminum oxide, silicon dioxide, ceramics, magnesium chloride, calcium carbonate, or dipotassium oxide.
[0091] In certain embodiments or examples, the catalyst support material may be selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel modified aluminum oxide silicon oxide, or zeolite.
[0092] In certain embodiments or examples, the binder may be selected from the group including hydroxypropyl cellulose, methyl cellulose, polyester, polyurethane, acrylic resin, condensation resin, polyvinyl acetate, sodium poly(acrylic acid), polyvinylidene fluoride, polyethylene oxide, polyethylene glycol, dextrin, sodium silicate, colloidal silica, polydimethylsiloxane, boehmite, colloidal aluminum oxide, or polyisobutylene.
[0093] In one embodiment or example, the catalyst particles are formed from a catalyst material or catalyst support material that includes a catalyst material on a support material. In one embodiment or example, the catalyst particles can be in the range of 0.1 nm to 10 mm, 1 nm to 5 mm, 100 nm to 1 mm, 1 μm to 200 μm, 0.25 μm to 50 μm, or 0.5 μm to 5 μm. The catalyst particles can be less than 5 mm, 1 mm, 100 μm, 10 μm, 5 μm, 1 μm, 500 nm, 250 nm, 100 nm, or 50 nm. The catalyst particles can be at least 0.1 nm, 1 nm, 10 nm, 100 nm, 250 nm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, or 50 μm. The catalyst particles can be in the range provided by any two of these upper and / or lower limits.
[0094] In some embodiments or examples, the coating thickness may be between about 1 μm and about 50 μm. The coating thickness may be in the range of 1-40%, 2-35%, 5-30%, 10-25%, or 15-20%. The coating thickness may be at least 1%, 5%, 10%, 15%, 20%, 35%, 30%, 35%, or 40%. The coating thickness may be less than 50%, 40%, 30%, 20%, 15%, 10%, 5%, or 3%. The coating thickness may be in the range provided by any two of these upper and / or lower limits.
[0095] In some embodiments or examples, the process further comprises a drying step. The drying step comprises the steps of: (a) applying a first temperature in the range of about 15°C to about 30°C to the coated surface of the scaffold for a first period of about 4-24 hours to volatilize at least a portion of the volatile materials from the catalytic liquid suspension, and (b) applying a second temperature in the range of about 100°C to about 180°C under reduced pressure for a second period of about 4-24 hours to form a dry coating on the surface of the scaffold. The first temperature may be in the range of 15°C to 30°C or 20°C to 25°C. For example, the temperature may be ambient temperature. The first temperature may be less than 30°C, 28°C, 26°C, 24°C, 22°C, 20°C, 18°C, or 16°C. The first temperature may be at least 15°C, 17°C, 19°C, 21°C, 23°C, 25°C, or 27°C. The first temperature may be in a range provided by any two of these upper and / or lower limits. The first period may be in a range of 4 to 24 hours or 10 to 20 hours. The first period may be less than 30, 28, 26, 24, 22, 20, 18, 16, 14, 12, 10, or 8 hours. The first period may be at least 5, 7, 9, 11, 13, 15, 17, 19, 21, 23, or 25 hours. For example, the first period may be 24 hours. The first period may be in a range provided by any two of these upper and / or lower limits. The second temperature may be in a range of 100°C to 180°C or 110°C to 140°C. The second temperature may be less than 180°C, 170°C, 160°C, 140°C, 120°C, or 110°C. The second temperature may be at least 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, or 130°C. For example, the temperature may be 120°C. The second temperature may be in a range provided by any two of these upper and / or lower limits. The second period of time may be in a range of 4 to 24 hours or 10 to 20 hours. The second period of time may be less than 30, 28, 26, 24, 22, 20, 18, 16, 14, 12, 10, or 8 hours. The second period of time may be at least 5, 7, 9, 11, 13, 15, 17, 19, 21, 23, or 25 hours.The second period of time may be a range provided by any two of these upper and / or lower limits.
[0096] The static mixer is for use in continuous flow chemical reaction systems and processes. The process may be an in-line continuous flow process. The in-line continuous flow process may be a recycle loop process or a single pass process. In one embodiment, the in-line continuous flow process is a single pass process.
[0097] As described above, a chemical reactor equipped with a static mixer scaffold can carry out heterogeneous catalytic reactions continuously. The chemical reactor can use single-phase or multi-phase feed and product streams. In one embodiment, the substrate feed (comprising one or more reactants) can be provided as a continuous fluid stream, for example, a) as a liquid stream containing the substrate as a solute in a suitable solvent, or b) as a liquid stream containing the liquid substrate with or without a co-solvent. It will be understood that the continuous fluid stream can be provided by at least one liquid phase. It will be understood that the fluid stream can be provided by one or more gas streams or sources thereof, such as, for example, hydrogen gas. The substrate feed is pumped into the reactor using a pressure-driven flow, for example, by a piston pump.
[0098] The % volume displacement of the static mixer relative to the reactor chamber for housing the mixer ranges from 1 to 40, 2 to 35, 3 to 30, 4 to 25, 5 to 20, or 10 to 15. The % volume displacement of the static mixer relative to the reactor chamber for housing the mixer may be less than 40%, 35%, 30%, 25%, 20%, 15%, 10%, or 5%.
[0099] A static mixer (CSM) configuration may be provided to enhance cross-sectional microscopic turbulence. Such turbulence may result from a variety of sources, such as the geometry of the CSM, or microscopic roughness of the CSM surface resulting from the 3D printing process. For example, the length scale of the turbulence may be reduced to provide better mixing. The length scale of the turbulence may be, for example, a microscopic length scale.
[0100] The static mixer configuration may provide for improved heat transfer characteristics within the reactor, such as reducing temperature differences at the exit cross-section. The heat transfer of the CSM may provide, for example, a cross-sectional or transverse temperature profile having a temperature difference of less than about 20° C. / mm, 15° C. / mm, 10° C. / mm, 9° C. / mm, 8° C. / mm, 7° C. / mm, 6° C. / mm, 5° C. / mm, 4° C. / mm, 3° C. / mm, 2° C. / mm, or 1° C. / mm.
[0101] The scaffolding may be configured such that, in use, the pressure drop (i.e., back pressure) across the static mixer (in Pa / m) is in the range of about 0.1 to 1,000,000 Pa / m (i.e., 1 MPa / m), including any value or range of values therebetween. For example, the pressure drop (i.e., back pressure) across the static mixer (in Pa / m) may be less than about 500,000, 250,000, 100,000, 50,000, 10,000, 5,000, 1,000, 750, 500, 250, 100, 75, 50, 25, 20, 15, 10, or 5 Pa / m. The static mixer may be configured to provide a lower pressure drop for a particular flow rate. In this regard, the static mixers, reactors, systems, and processes described herein may be provided with parameters suitable for industrial applications. The above pressure drops can be maintained when the volumetric flow rate is at least 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 10, 20, 30, 40, 50, 100, 500, 1000 ml / min.
[0102] The catalytic reaction may be a hydrogen insertion reaction involving the use of a hydrogenation catalyst. The hydrogen insertion or hydrogenation catalyst facilitates the insertion of hydrogen into the intramolecular bond of the reactant, for example, a carbon-oxygen bond to form an oxygen-containing organic material as described above, the conversion of an unsaturated bond to a saturated bond, the removal of a protecting group, for example, the conversion of an O-benzyl group to a hydroxyl group, or the reaction of a nitrogen triple bond to form ammonia or hydrazine or a mixture thereof. The hydrogen insertion or hydrogenation catalyst may be selected from the group consisting of cobalt, ruthenium, osmium, nickel, palladium, platinum, and alloys, compounds, and mixtures thereof. In an embodiment, the hydrogen insertion or hydrogenation catalyst comprises or consists of platinum or titanium. In ammonia synthesis, the catalyst may facilitate the dissociative adsorption of the hydrogen and nitrogen species sources for subsequent reactions. In a further embodiment, the hydrogen insertion or hydrogenation catalyst is coated using wash coating or dip coating.
[0103] Static Mixer It will be appreciated that the static mixer may provide an integral scaffolding for the chemical reactor chamber. A static mixer scaffolding for a continuous flow chemical reactor chamber may include a catalytically active scaffold defining a plurality of passages configured to disperse and mix one or more fluid reactants during flow and reaction through the mixer. It will be appreciated that at least a substantial portion of the surface of the scaffolding may include a catalytic material. The catalytic material may be selected from at least one of metals, metal oxides, aluminum silicates, activated carbon, mesoporous carbon, graphene, graphitic materials, metal organic frameworks, zeolites to provide catalytic reactive sites on the surface of the static mixer scaffolding.
[0104] The static mixer may be provided as one or more scaffolds, each configured for insertion into a continuous flow chemical reactor or its reactor chamber. The static mixer scaffold may be configured as a modular insert for assembly into a continuous flow electrochemical reactor or its chamber. The static mixer scaffold may be configured as an insert for an in-line continuous flow chemical reactor or its chamber. The in-line continuous flow chemical reactor may be a recycle loop reactor or a single pass reactor. In one embodiment, the in-line continuous flow chemical reactor is a single pass reactor.
[0105] The static mixer scaffold may be configured to enhance mixing and heat transfer properties for redistributing fluids in directions across the main flow, e.g., radial and tangential or azimuthal directions relative to the central longitudinal axis of the static mixer scaffold. The static mixer scaffold may be configured for at least one of: (i) ensuring that as much catalytic surface area as possible is presented to the flow so that close to the maximum number of reaction sites are activated; and (ii) improving mixing of the flow so that (a) reactant molecules come into contact with the surface of the static mixer scaffold more frequently, and (b) heat is efficiently transferred from or to the fluid. The static mixer scaffold may be provided with a variety of geometric configurations or aspect ratios that correlate with the particular application. The static mixer scaffold allows the fluid reactants to mix and be in close proximity to the catalytic material for activation. The static mixer scaffold may be configured for use with turbulent flow rates, e.g., to enhance turbulence and mixing even at or near the interior surface of the reactor chamber housing. It will also be appreciated that the static mixer scaffolding may be configured to enhance heat and mass transfer characteristics of both laminar and turbulent flow.
[0106] The configuration may also be designed to improve efficiency, extent of chemical reaction, or other characteristics, such as pressure drop (while maintaining a given or desired flow rate), residence time distribution, or heat transfer coefficient. As previously discussed, conventional static mixers have not heretofore been developed to specifically address the enhanced heat transfer requirements that may result from the catalytic reaction environment provided by the static mixers of the present invention.
[0107] The configuration of the scaffold, or static mixer, can be determined using computational fluid dynamics (CFD) software that can be used to improve the configuration for mixing of reactants to improve contact and activation of the reactants or their reactive intermediates at the catalytically reactive sites of the scaffold. CFD-based configuration determination is described in more detail in the following section.
[0108] The scaffold of the static mixer may be formed by additive manufacturing. The static mixer may be an additively manufactured static mixer. Additive manufacturing of the static mixer and subsequent catalytic coating may provide a static mixer configured for efficient mixing, heat transfer, and catalytic reactions (of reactants in a continuous flow chemical reactor), which may be physically tested for reliability and performance, and optionally further redesigned and reconfigured using additive manufacturing (such as 3D printing) techniques. Additive manufacturing provides flexibility in preliminary design and testing of the static mixer, as well as in further redesign and reconfiguration, facilitating the development of more commercially viable and durable static mixers.
[0109] The static mixer scaffold may be provided in a configuration selected from one or more of the following general, non-limiting, exemplary configurations: Open configuration with helix Open configuration with blades ·Corrugated Plate ·Multi-layer design Closed configuration with channels or holes Irregular designs such as metal foams or monoliths.
[0110] The static mixer scaffold may be provided in a mesh configuration having a plurality of integral units defining a plurality of passageways configured to facilitate mixing of one or more fluid reactants.
[0111] The static mixer scaffold may comprise a scaffold provided by a lattice of interconnected segments configured to define a plurality of apertures to facilitate mixing of the fluids flowing through the reactor chamber. The scaffold may also be configured to facilitate heat transfer as well as fluid mixing.
[0112] In various embodiments, the shape or configuration may be selected to enhance one or more properties of the static mixer scaffold selected from specific surface area, volumetric displacement ratio, strength and stability to high flow rates, suitability for fabrication using additive manufacturing, as well as to achieve one or more of the following: advanced chaotic advection, turbulent mixing, catalytic interaction, and heat transfer.
[0113] In some embodiments, the scaffold may be configured to enhance chaotic advection or turbulent mixing, such as cross-sectional, transverse (relative to the flow), or localized turbulent mixing. ,vinegar The flow is controlled within a given length along the longitudinal axis of the static mixer scaffold. 、 More than a certain number of times, e.g. 200m -1 More than 400m optional -1 More than 800m optional -1 More than 1500m optional -1 More than 2000m optional -1 More than 2500m optional -1 More than 3000m optional -1 More than 5000m optional -1 More To change the local flow direction, or Local flowThe shape or configuration of the scaffold may be such that more than a certain number of split structures, e.g., 100 m, are present within a given volume of the static mixer. -3 More than 1000m optional -3 More, optionally 1×10 4 m -3 More, optionally 1×10 6 m -3 More, optionally 1×10 9 m -3 More, optionally 1×10 10 m -3 More flow splitting structures may be provided.
[0114] The shape or configuration of the scaffold may be substantially tubular or linear. The scaffold may be formed from or may include multiple segments. Some or all of the segments may be straight segments. Some or all of the segments may include polygonal prisms, such as rectangular prisms. The scaffold may include multiple planar surfaces. The straight segments may be disposed at an angle relative to one another. The straight segments may be disposed at a number of different angles, such as, for example, two, three, four, five, or six different angles, relative to the longitudinal axis of the scaffold. The scaffold may comprise a repeating structure. The scaffold may comprise a number of similar structures that are periodically repeated along the longitudinal axis of the scaffold. The shape or configuration of the scaffold may be consistent along the length of the scaffold. The shape of the scaffold may vary along the length of the scaffold. The straight segments may be connected by one or more curved segments. The scaffold may include one or more helical segments. The scaffold may generally define a helix. The scaffold may comprise a helix comprising a plurality of apertures on a surface of the helix.
[0115] The dimensions of the static mixer may vary depending on the application. The static mixer or the reactor comprising the static mixer may be tubular. The tube of the static mixer or reactor may, for example, have a diameter in the range of 1 to 5000, 2 to 2500, 3 to 1000, 4 to 500, 5 to 150, or 10 to 100 mm. The tube of the static mixer or reactor may, for example, have a diameter of at least about 1, 5, 10, 25, 50, 75, 100, 250, 500, or 1000 mm. The tube of the static mixer or reactor may, for example, have a diameter of less than about 5000, 2500, 1000, 750, 500, 250, 200, 150, 100, 75, or 50 mm. The aspect ratio (L / d) of the static mixer scaffold, or the reactor chamber comprising the static mixer scaffold, can be provided in a range suitable for industrial-scale flow rates for a particular reaction. The aspect ratio can be, for example, in the range of about 1-1000, 2-750, 3-500, 4-250, 5-100, or 10-50. The aspect ratio can be, for example, less than about 1000, 750, 500, 250, 200, 150, 100, 75, 50, 25, 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, or 2. The aspect ratio can be, for example, greater than about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 50, 75, or 100. It will be understood that aspect ratio refers to the ratio of length to diameter (L / d) of a single unit or scaffold.
[0116] Static mixer platforms or reactors generally have a high specific surface area (i.e., the ratio between the internal surface area and the volume of the static mixer platform and reactor chamber). The specific surface area may be smaller than that provided by packed bed reactor systems. The specific surface area (m 2 m -3 ) can be in the range of 100 to 40,000, 200 to 30,000, 300 to 20,000, 500 to 15,000, or 12000 to 10,000. 2 m -3) may be at least 100, 200, 300, 400, 500, 750, 1000, 2000, 3000, 4000, 5000, 7500, 10000, 12500, 15000, 17500, or 20000. It will be appreciated that the specific surface area may be measured by a number of techniques, including the BET isotherm technique.
[0117] The static mixer scaffolding may be configured to improve properties such as mixing and heat transfer for laminar or turbulent flow rates. It will be appreciated that for Newtonian fluids flowing in hollow pipes, the correlation between laminar and turbulent flow and Reynolds number (Re) values typically results in laminar flow rates when Re is less than 2300, transient flow rates when Re is greater than 2300 and less than 4000, and turbulent flow rates when Re is greater than 4000. The static mixer scaffolding may be configured to provide improved properties selected from one or more of mixing, reactivity, heat transfer, and pressure drop for laminar or turbulent flow rates. It will be appreciated that further improvements to certain types of chemical reactions require their own specific considerations.
[0118] The static mixer scaffold may generally be configured to operate at a Re of at least 0.01, 0.1, 1, 5, 50, 100, 150, 200, 250, 300, 350, 400, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000. The static mixer scaffold may be configured to operate in a generally laminar Re range of about 0.1-2000, 1-1000, 10-800, or 20-500. The static mixer scaffold may be configured to operate in a generally turbulent Re range of about 1000-15000, 1500-10000, 2000-8000, or 2500-6000.
[0119] The % volume displacement of the static mixer relative to the reactor chamber for housing the mixer ranges from 1 to 40, 2 to 35, 3 to 30, 4 to 25, 5 to 20, or 10 to 15. The % volume displacement of the static mixer relative to the reactor chamber for housing the mixer may be less than 40%, 35%, 30%, 25%, 20%, 15%, 10%, or 5%.
[0120] The static mixer configuration may be provided to enhance microscopic turbulence in the cross section. Such turbulence may result from a variety of sources, such as the geometry of the CSM, or microscopic roughness of the CSM surface due to the 3D printing process and / or surface coatings. For example, the length scale of the turbulence may be reduced to provide better mixing. The length scale of the turbulence may be, for example, in the range of microscopic length scales.
[0121] The static mixer configuration may provide for improved heat transfer characteristics within the reactor, such as reducing temperature differences at the exit cross-section. The heat transfer of the CSM may provide, for example, a cross-sectional or transverse temperature profile having a temperature difference of less than about 20° C. / mm, 15° C. / mm, 10° C. / mm, 9° C. / mm, 8° C. / mm, 7° C. / mm, 6° C. / mm, 5° C. / mm, 4° C. / mm, 3° C. / mm, 2° C. / mm, or 1° C. / mm.
[0122] The scaffolding may be configured such that, in use, the pressure drop (i.e., pressure differential or back pressure) (in Pa / m) across the static mixer is in the range of about 0.1 to 1,000,000 Pa / m (i.e., 1 MPa / m), including any value or range of values therebetween. For example, the pressure drop (in Pa / m) across the static mixer may be less than about 500,000, 250,000, 100,000, 50,000, 10,000, 5,000, 1,000, 750, 500, 250, 100, 75, 50, 25, 20, 15, 10, or 5 Pa / m. The static mixer may be configured to provide a lower pressure drop for a particular flow rate. In this regard, the static mixers, reactors, systems, and processes described herein may be provided with parameters suitable for industrial applications. The above pressure drops can be maintained when the volumetric flow rate is at least 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 10, 20, 30, 40, 50 ml / min.
[0123] Static mixer preparation process The scaffolding of the static mixer may be provided by additive manufacturing, such as 3D printing. Additive manufacturing of the static mixer and subsequent catalyst coating may provide a static mixer configured for efficient mixing, heat transfer, and catalytic reactions (of reactants in a continuous flow chemical reactor) that may be physically tested for reliability and performance, and optionally further redesigned and reconfigured using additive manufacturing (e.g., 3D printing) techniques. Following the original design and development using additive manufacturing, other manufacturing processes such as casting (e.g., investment casting) may be used to prepare the static mixer. Additive manufacturing provides flexibility in the preliminary design and testing of the static mixer, as well as in further redesign and reconfiguration, facilitating the development of more commercially viable and durable static mixers.
[0124] The static mixer scaffold can be manufactured by additive manufacturing (i.e., 3D printing) technology. For example, an electron beam 3D printer or a laser beam 3D printer may be used. The additive material of the 3D printing may be, for example, a titanium alloy-based powder (e.g., in the range of 45-105 micrometer diameter), or a cobalt-chromium alloy-based powder (e.g., FSX-414), or a stainless steel or aluminum-silicon alloy. The powder diameter associated with a laser beam printer is usually smaller than that used in an electron beam printer.
[0125] 3D printing is well understood and refers to the process of sequentially depositing material into a powder bed, either through fusion facilitated by heat delivered by a beam or by extrusion and sintering-based processes. 3D printable models are typically created using a computer-aided design (CAD) package. Before printing the 3D model from the STL file, it is typically inspected for errors and corrections of the applied manifold. Once that is complete, the .STL file is processed by software called a "slicer", which converts the model into a series of thin layers and generates a G-code file with instructions tailored to a specific type of 3D printer. The 3D printing process is advantageous to use for the preparation of static mixer scaffolds, as it eliminates the product design limitations imposed by traditional manufacturing routes. As a result, the design freedom inherited from 3D printing allows the static mixer's shape to be further optimized for performance than would otherwise be the case.
[0126] The catalytically active scaffold may be prepared from a catalytic material selected from at least one of metals, metal oxides, aluminum silicates, activated carbon, mesoporous carbon, graphene, graphitic materials, metal-organic frameworks, and zeolites. The process of preparing the static mixer may include applying a coating comprising a catalytic material to at least a substantial portion of the scaffold by wash coating or dip coating. For example, the coating may be provided on at least 50% of the surface of the scaffold. In other embodiments, the coating may be provided on at least 60%, 70%, 80%, 90%, 95%, 98, or 99% of the surface of the scaffold.
[0127] In some embodiments, the process may involve first forming a scaffold using an additive manufacturing process, such as 3D printing. EXAMPLES
[0128] The present disclosure is further illustrated by the following examples. It should be understood that the following descriptions are merely for the purpose of illustrating certain embodiments, and are not intended to be limiting with respect to the above descriptions.
[0129] The present disclosure provides an effective and scalable process for depositing catalytic or catalyst support materials onto a static mixer scaffold by washcoating / dipcoating the static mixer scaffold in a catalytic liquid suspension. With reference to Figure 1, this process may include several different deposition processes, namely option (a), option (b), option (c), and option (d), depending on the type of catalytic or catalyst support material that needs to be coated onto the static mixer scaffold.
[0130] It will be appreciated that the static mixer scaffold may be exposed to any of a variety of surface pretreatment methods to prepare the surface for catalytic coating.
[0131] Example 1 Optional pre-treatment steps: 1) To etch the surface of the static mixer scaffold, the scaffold is first immersed in a dilute HCl solution (5-10 wt%) for 1 h. 2) The scaffold is then immersed in a sonication bath for 20 minutes. 3) The scaffold is immersed in an acetone solution for 10 minutes. 4) Dry the scaffold in an oven at 140°C for 16 hours.
[0132] Example 2 General wash coating steps for coating options (a)-(d): Option (a) 1) To form a catalytic liquid suspension, a quantity of commercially available catalytic material or catalytic support material with controlled particle size (usually less than 5 μm, by dry / wet milling as necessary) was added to a quantity of solvent and stirred with a magnetic stirrer for 48 hours to achieve a homogenous slurry at a concentration of about 3-25% by weight of solids. 2) The pretreated static mixer scaffold is immersed in the suspension for 20-30 seconds, followed by a blow of pressurized air to eliminate excess liquid and prevent channel blockage in the scaffold. The immersed scaffold is then placed horizontally in an open container at room temperature for 1 day to allow the remaining solvent to evaporate. Finally, the scaffold is placed in an oven under vacuum at 120 °C to remove the residual solvent. This process was repeated 2-6 times to obtain more catalyst deposition layers on the catalytic static mixer scaffold or until the desired catalyst loading was achieved.
[0133] Option (b) 1) Liquid support suspension The support material is stirred with a magnetic stirrer for 24 hours to form a homogenous slurry in a volume of solvent, with a concentration of approximately 10-25% by weight of solids. The pretreated static mixer scaffolds were immersed in the liquid support suspension for 20-30 seconds, followed by a blow of pressurized air to displace excess liquid and prevent channel blockage in the scaffold. The immersed scaffolds were then placed horizontally in an open container at room temperature for 1 day to allow most of the solvent to evaporate in the air. The scaffolds were then placed in an oven under vacuum at 120 °C to remove residual solvent. 2) Step 1 forms an intermediate support layer prior to coating with the catalytic liquid suspension. 3) To form a catalytic liquid suspension, a quantity of commercially available catalytic material or catalytic support material with controlled particle size (usually less than 5 μm, by dry / wet milling as necessary) was added to a quantity of solvent and stirred with a magnetic stirrer for 48 hours to achieve a homogenous slurry at a concentration of about 3-25% by weight of solids. 4) The static mixer scaffold, previously coated with the intermediate support layer, is immersed in the suspension for 20-30 seconds, followed by a blow of pressurized air to eliminate excess liquid and prevent channel blockage in the scaffold. The immersed scaffold is then placed horizontally in an open container at room temperature for one day, thereby evaporating the remaining solvent. Finally, the scaffold is placed in an oven under vacuum at 120 °C to remove the residual solvent. This process was repeated 2-6 times to obtain more catalyst deposition layers on the catalytic static mixer scaffold or until the desired catalyst loading was achieved.
[0134] Option (c) 1) Liquid Support Suspension The support material and binder are stirred with a magnetic stirrer for 24 hours to form a homogenous slurry at approximately 1% by weight in a volume of solvent, with a concentration of approximately 10-25% by weight of solids. The pretreated static mixer scaffolds were immersed in the liquid support suspension for 20-30 seconds, followed by a blow of pressurized air to displace excess liquid and prevent channel blockage in the scaffold. The immersed scaffolds were then placed horizontally in an open container at room temperature for 1 day to allow most of the solvent to evaporate in the air. The scaffolds were then placed in an oven under vacuum at 120°C to remove residual solvent. 2) Step 1 forms an intermediate support layer prior to coating with the catalytic liquid suspension. 3) To form a catalytic liquid suspension, a quantity of commercially available catalytic material or catalytic support material (with controlled particle size) (usually less than 5 μm, by dry / wet milling as required) is added to a quantity of solvent and stirred with a magnetic stirrer for at least 48 hours to achieve a homogenous slurry with a concentration of about 3-25% by weight of solids. 4) The static mixer scaffold, previously coated with an intermediate support layer, was immersed in the suspension for 20-30 seconds and then blown with pressurized air to eliminate excess liquid and prevent channel blockage in the scaffold. The immersed scaffold was then placed horizontally in an open container at room temperature for 1 day to allow the remaining solvent to evaporate. Finally, the scaffold was placed in an oven under vacuum at 120 °C to remove the residual solvent. This process was repeated 2-6 times to obtain more catalyst deposition layers on the catalytic static mixer scaffold or until the desired catalyst loading was achieved.
[0135] Option (d) 1) To form a catalytic liquid suspension, a quantity of commercially available catalyst material or catalyst support material with controlled particle size (usually less than 5 μm, by dry / wet milling as needed) and about 1 wt. % of binder are added to a quantity of solvent and stirred with a magnetic stirrer for 48 hours to achieve a homogenous slurry at a concentration of about 3-25 wt. % of solids. 2) The pretreated static mixer scaffold is immersed in the suspension for 20-30 seconds, followed by a blow of pressurized air to eliminate excess liquid and prevent channel blockage in the scaffold. The immersed scaffold is then placed horizontally in an open container at room temperature for 1 day to allow the remaining solvent to evaporate. Finally, the scaffold is placed in an oven under vacuum at 120 °C to remove the residual solvent. This process was repeated 2-6 times to obtain more catalyst deposition layers on the catalytic static mixer scaffold or until the desired catalyst loading was achieved.
[0136] Example 3 Adhesion Test The solid content was checked by placing a few drops of the slurry on a glass dish and drying it in an oven under vacuum at 120° C. The total solid content can be calculated by equation (1), where m1 is the mass of the empty glass dish, m2 is the mass of the glass dish with the slurry, and m3 is the mass after evaporation of the solvent. The homogeneity of the slurry can also be estimated by several parallel solid content tests.
number
number
number
[0137] Example 4 Flow Reactor Testing The continuous flow reactor setup used for the evaluation has been described in previous studies, including WO2017106916. It consists of a hydrogen reactor module housing the catalyst insert, a gas handling system, a liquid delivery system (reagent pumps, driven by Gilson 305 HPLC pumps), and electronic process control and data logging.
[0138] The reactor module contains 12 reactor zones, each made of 15 cm long stainless steel tubing (Swagelok, 8 mm OD, 6 mm ID), and five temperature probes (PT-100) placed along the length of the eth reactor path.
[0139] The reactor module can be easily disassembled to facilitate switching of catalyst inserts. Reagent pumps provide the substrate feed stream, which contains a solution of the starting material substrate, either neat or in a solvent. Hydrogen gas is supplied from a hydrogen cylinder (G-type cylinder) and is mixed with the liquid stream in a T-piece. Pressure in the reactor is regulated by a diaphragm backpressure regulator (BPR, Swagelok KBP1J0A4D5A20000) at the reactor outlet.
[0140] After passing through the BPR, the hot effluent can optionally be cooled in a coil-type heat exchanger, which can be powered with a suitable cooling fluid. The product stream is then collected in a bottle or flask for further workup and analysis.
[0141] The following additional safety components and process control and monitoring equipment are installed on the rig: safety pressure relief valves at the reactor inlet (Swagelok, SS-4R3A), safety shut-off valves on the gas lines (Burkert, 2 / 2 way solenoid valves 6027-A03), flashback arrestors on the gas lines (Witt 85-10), mass flow controllers on the gas lines (Bronkhorst, MFC F-201CV-500), and pressure sensors in the liquid lines, gas lines, and reactor inlet.
[0142] The reaction occurs at the solid-liquid interface of the catalyst insert in the reactor zone. The operation of the reactor system is controlled by a proprietary LabView software. Temperature, pressure, and gas flow rates are also monitored by the LabView control program.
[0143] To evaluate the hydrogenation reactions of this reactor, a series of experiments were carried out to investigate the hydrogenation of vinyl acetate (VAc), cinnamaldehyde (CAL), (-)-isopulegol (IPG), 1,4-butynediol (BYD), and 2-methyl-3-butyn-2-ol (MBY) using the solvents ethanol (EtOH), methanol (MeOH), isopropanol (iPrOH), n-heptane, or ethyl acetate (EtOAc), see Scheme 1. [ka]
[0144] A typical hydrogenation reaction with the above reactor configuration was carried out as follows: First, the four catalyst inserts in the reactor were heated to 24 bar, 120° C., and 190 mL. N Activation was performed by flowing hydrogen at a gas flow rate of 10000 / min. The activation reactor was flushed with the solvent EtOH using a liquid reagent pump. The substrate, VAc, was dissolved in EtOH at a concentration of 2 mol / L.
[0145] Before the start of the reaction, hydrogen gas was introduced along with the washing solvent EtOH, and the reaction parameters were adjusted: pressure in the reactor, p R= 20 bar, liquid flow rate, V L = 1 ml / min, gas flow rate V G =50mL N / min, and reactor temperature, T R = 120 °C. Once the pressure and temperature were stabilized, the substrate (VAc) was fed to the reactor by switching the reagent pump from the pure solvent to the prepared clear stock solution. The clear product was collected in several fractions at the outlet of the reactor and then 1 The reaction was analyzed by H-NMR and GC. The reaction conversion was recorded on a Bruker AC-400 spectrometer in deuterated chloroform (Cambridge Isotope Laboratories Inc.). 1 The composition was calculated from H NMR spectrum. The residual solvent peak at δ=7.26 ppm was used as an internal reference. The product composition was analyzed by GC-FID and GC-MS.
[0146] GC-FID results were also used to confirm NMR conversion and to calculate GC-based yields. GC-mass spectra were acquired using a Perkin Elmer Clarus 600 GC mass spectrometer using electron impact ionization in positive ion mode at 70 eV ionization energy. Gas chromatography was performed using a Perkin Elmer Elite-5MS GC column (30 mx0.25 mm ID, 0.25 μm film thickness) with a temperature program of 40°C for 2 min, then heated at 10°C / min to 280°C, where the temperature was held for 4 min at a split ratio of 70, injector temperature at 250°C, and the transfer line was set to 250°C. Ultra-high purity helium was used as the carrier gas at a flow rate of 0.7 ml / min.
[0147] GC-FID analysis was performed on an Agilent 6850 Series II gas chromatograph equipped with a split / splitless inlet and a detector temperature of 250°C. Separation was performed on a Grace BPX5 capillary column (25m x 0.32mm ID, 0.50μm film thickness) with a temperature program of 40°C for 2 min, then heated at 10°C / min to 280°C, where the temperature was held for 4 min with a split ratio of 50 and an injector temperature of 200°C. High purity helium was used as the carrier gas with a flow rate of 2.4ml / min. Reagents VAc, CAL, BYD, and MBY were obtained from Sigma Aldrich. Solvents EtOH, MeOH, iPrOH, n-heptane, and EtOAc were obtained from MerckKGaA. All reagents and solvents were used without further purification.
[0148] Table 5 shows experimental data from the hydrogenation reactions of VAc and CAL, and from the hydrogenation reaction of (-)-isopulegol (IPG) to form (-)-menthol (MEN). Table 6 shows experimental data for the semi-hydrogenation reaction of BYD to BED. Table 7 shows experimental data for the semi-hydrogenation reaction of MBY to MBE. The experimental data advantageously demonstrate that high conversions (VAc: up to 100%, CAL: up to 100%, BYD: up to 100%, MBY: up to 100%) and high selectivities (BYD: up to 92%, MBY: up to 100%) can be achieved using the coated catalytic static mixer scaffold (CSM) described herein. The space-time yields of catalytic static mixer reactors for these reactions were in the range of a few kg / L h (VAc: up to 1.68 kg / L h, CAL: up to 0.70 kg / L h, BYD: up to 1.85 kg / L h, MBY: up to 3.22 kg / L h). [Table 5] [Table 6-1] [Table 6-2] [Table 6-3] [Table 6-4] [Table 6-5] [Table 7-1] [Table 7-2] [Table 7-3] [Table 7-4]
[0149] Example 5 Leaching Analysis Collection of product solutions during the steady-state regime of extended runs allowed for catalyst leaching analysis of catalytic static mixer scaffolds (CSMs).
[0150] A total of over 1 L of product solution was collected during the experiment for the standard test reaction, i.e., reduction of VAc to EtOAc in ethanol. All organic material was carefully removed and the remaining material was analyzed by inductively coupled plasma-optical emission spectroscopy (ICP-EOS) for the presence of Cr, Mn, Fe, Mo, Al, Ni, Pd, Pt, and Ru. All CSMs tested were wash-coated alumina type catalysts, (1) nickel on aluminum oxide, (2) palladium on aluminum oxide, (3) platinum on aluminum oxide, and (4) ruthenium on aluminum oxide, and four different sets of CSMs (1)-(4) were tested, respectively. Each CSM was 6 mm in diameter and 150 mm in length. As shown in Table 7 below, the product stream contained only parts per billion (ppb) levels of the active catalytic metals Ni, Pd, Pt, and Ru. It will be appreciated that the ppb values for Cr, Mn, Fe, Mo, and Al come from the 316 stainless steel body and base static mixer scaffolding of the reactor. It will also be appreciated that the ppb levels of the active metals, Ni, Pd, Pt, and Ru, come from the catalytic coatings deposited on the CSM.
[0151] The results unexpectedly and advantageously show that the active catalyst layer exhibits excellent adhesion to the base static mixer scaffolding and that degradation of the catalyst layer of the CSM during continuous use over extended periods of time is negligible. In all examples shown in Table 8 below, the highest amount of soluble metal detected was Fe, and therefore it is believed that the majority of the metal contamination originates from the 316 stainless steel (SS) CSM scaffolding, SS piping, and other SS parts of the reactor. [Table 8] The following is a summary of the claims as originally filed: [1] A process for preparing a catalytically coated scaffold comprising the steps of: (i) applying a catalytic liquid suspension to a surface of a scaffold to provide a coating comprising catalytically reactive sites on the surface of the coated scaffold, wherein the catalytic liquid suspension comprises a liquid carrier comprising a plurality of ex situ catalyst particles, and wherein the coated scaffold has a non-line-of-sight configuration including a plurality of passageways configured to disperse and mix one or more fluid reactants during flow and reaction thereof; and (ii) drying the coated scaffold to remove the liquid carrier and provide a coated scaffold comprising ex situ catalyst particles; The process comprising: [2] The process of [1], wherein the scaffold is a static mixer scaffold. [3] The process of [2], wherein the surface of the static mixer is pre-coated with a support material and optionally a binder prior to step (i). [4] The process according to any one of [1] to [3], wherein the catalytic liquid suspension further comprises a binder. [5] The process described in any one of [1] to [4], wherein the step of applying the catalytic liquid suspension to the surface of the scaffold in step (i) is by wash coating or dip coating. [6] The process described in any one of [1] to [5], wherein the process further comprises a pretreatment step prior to applying the catalytic liquid suspension to the surface of the scaffold in step (i), the pretreatment step comprising at least one surface treatment step on the surface of the scaffold selected from chemical treatment, anodizing, hot dip plating, vacuum plating, painting, thermal spraying, and acid etching. [7] The process of any one of [1] to [6], wherein the catalyst particles are formed from a catalyst support material comprising a catalyst material or a catalyst material on a support material. [8] The process of [7], wherein the catalytic material is selected from a metal, a metal oxide, an aluminum silicate, an activated carbon, a mesoporous carbon, a graphene, a graphitic material, a metal organic framework, a zeolite, or any combination thereof. [9] The process of [8], wherein the metal is selected from at least one of aluminum, iron, cerium, calcium, cobalt, copper, magnesium, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or a metal oxide thereof.
[10] The process according to any one of [3] to [9], wherein the support material is selected from at least one of activated carbon, mesoporous carbon, graphene, graphite materials, metal organic frameworks, zeolites, aluminum oxide, silicon dioxide, ceramics, magnesium chloride, calcium carbonate, or dipotassium oxide.
[11] The process according to any one of [7] to
[10] , wherein the catalyst support material is selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel modified aluminum oxide, silicon oxide, or zeolite.
[12] The process according to any one of [1] to
[11] , wherein the concentration of the catalyst particles in the catalytic liquid suspension is less than 10 wt. %, based on the total weight of the catalytic liquid suspension.
[13] The process of any one of [3] to
[12] , wherein the binder for the catalytic liquid suspension is selected from the group including hydroxypropyl cellulose, methyl cellulose, polyester, polyurethane, acrylic resin, condensation resin, polyvinyl acetate, sodium poly(acrylic acid), polyvinylidene fluoride, polyethylene oxide, polyethylene glycol, dextrin, sodium silicate, colloidal silica, polydimethylsiloxane, boehmite, colloidal aluminum oxide, or polyisobutylene.
[14] The process of
[13] , wherein the binder is added at a concentration of between about 0.3% and about 5% by weight, based on the total weight of the catalytic liquid suspension.
[15] The process according to any one of [1] to
[14] , wherein the liquid carrier is selected from the group consisting of water, ethanol, isopropanol, butanol, ethyl acetate, acetone, or a combination thereof.
[16] The process of any one of [1] to
[15] , wherein the catalytic liquid suspension has a solids content of between about 3% and about 28% by weight.
[17] The process according to any one of [1] to
[16] , wherein the coating has a thickness between about 1 μm and about 50 μm.
[18] The catalyst has a surface area of about 1 m 2 / g and about 1000m 2 The process according to any one of [1] to
[17] , wherein the ratio of the above is between 0.01 and 0.1 / g.
[19] The process of any one of [1] to
[18] , wherein the adhesion of the coating results in a total mass loss of the coating of less than about 0.5 wt.% as measured by an ultrasonic treatment test.
[20] The process according to any one of [1] to
[19] , wherein the scaffold is a metal, a metal alloy, a cermet, a carbon fiber, silicon carbide or a polymer.
[21] The process of
[20] , wherein the scaffold is a metal scaffold.
[22] The process of
[20] , wherein the metal or metal alloy of the metal scaffold is titanium, aluminum or stainless steel.
[23] The process described in any one of [1] to
[22] , wherein the aspect ratio (L / d) of the scaffold is at least 75.
[24] The process of any one of [1] to
[23] , wherein the ex situ catalyst particles are less than about 5 μm.
[25] The process according to any one of [1] to
[24] , wherein the drying step comprises the steps of: (a) applying a first temperature ranging between about 15° C. and about 30° C. to the coated surface of the scaffold for a first period of about 4 to 24 hours to volatilize at least a portion of volatile materials from the catalytic liquid suspension; and (b) applying a second temperature in the range of between about 100° C. and about 180° C. under a controlled atmosphere for a second period of time of about 4 to 24 hours, such that a dry coating is formed on the surface of the scaffold.
[26] A catalytically coated scaffold prepared by the process for preparing the catalytically coated scaffold according to any one of [1] to
[25] .
[27] A catalytically coated scaffolding comprising a coating on a scaffolding, the coating comprising a plurality of catalytic particles, the coated scaffolding having a non-line-of-sight configuration including a plurality of passageways configured for dispersing and mixing one or more fluid reactants during flow and reaction thereof.
[28] The catalytically coated scaffold of
[27] , wherein the coating comprises a support material and optionally a binder.
[29] The catalytically coated scaffold of
[28] , wherein the catalytic particles are selected from metals, metal oxides, aluminum silicates, activated carbon, mesoporous carbon, graphene, graphitic materials, metal organic frameworks, zeolites, or any combination thereof.
[30] The catalytically coated scaffold of any one of
[27] to
[29] , wherein the catalytic particles are a metal selected from at least one of aminium, iron, cerium, calcium, cobalt, copper, magnesium, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or metal oxides thereof.
[31] The catalytically coated scaffold of
[28] , wherein the support material is selected from at least one of activated carbon, mesoporous carbon, graphene, graphite materials, metal organic frameworks, zeolites, aluminum oxide, silicon dioxide, ceramics, magnesium chloride, calcium carbonate, or dipotassium oxide.
[32] The catalytically coated scaffold of
[28] , wherein the catalytic support material is selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel modified aluminum oxide, silicon oxide, or a zeolite.
[33] The catalytically coated scaffold of any one of
[27] to
[32] , wherein the binder is selected from the group including hydroxypropyl cellulose, methyl cellulose, polyester, polyurethane, acrylic resin, condensation resin, polyvinyl acetate, sodium poly(acrylic acid), polyvinylidene fluoride, polyethylene oxide, polyethylene glycol, dextrin, sodium silicate, colloidal silica, polydimethylsiloxane, boehmite, colloidal aluminum oxide, or polyisobutylene.
[34] The catalytically coated scaffold described in any one of
[27] to
[33] , wherein the catalyst particles are less than 5 μm.
[35] The catalytically coated scaffold described in any one of
[27] to
[34] , wherein the thickness of the coating is between about 1 μm and about 50 μm.
[36] The catalytically coated scaffold described in any one of
[27] to
[35] , wherein the coated scaffold is a coated static mixer scaffold.
[37] A continuous flow chemical reactor for use in reacting one or more fluid reactants, the reactor comprising one or more catalytically coated scaffolds prepared by the process described in any one of [1] to
[26] , or a catalytically coated scaffold described in any one of
[27] to
[36] .
[38] The continuous flow chemical reactor of
[37] , wherein the one or more fluid reactants are provided as a continuous fluid stream.
[39] The continuous flow chemical reactor of any one of
[37] or 38, wherein the continuous fluid flow is provided by at least one liquid phase.
[40] A continuous flow process for heterogeneous reactions comprising one or more chemical reactors according to any one of
[37] to
[39] .
[41] The continuous flow process according to
[40] , wherein the heterogeneous reaction is a hydrogenation reaction.
Claims
1. A process for preparing a catalytically coated scaffold, said process comprising the following steps: (i) applying a catalytic liquid suspension to a surface of a scaffold to provide a coating comprising catalytically reactive sites on the surface of the coated scaffold, wherein the catalytic liquid suspension comprises a liquid carrier comprising a plurality of ex situ catalyst particles, and wherein the coated scaffold has a non-line-of-sight configuration including a plurality of passageways configured to disperse and mix one or more fluid reactants during their flow and reaction, said applying by redistributing the fluid transversely to a main stream of the flow by redirecting or splitting local flows more than 200 m −1 , corresponding to a number in a given length along a longitudinal axis of the coated scaffold; and (ii) drying the coated scaffold to remove the liquid carrier to provide a coated scaffold including ex situ catalyst particles; Equipped with applying said catalytic liquid suspension to the surface of said scaffold in step (i) is by wash-coating or dip-coating; the aspect ratio (L / d) of the scaffold is at least 15; the scaffold is a static mixer scaffold; A process wherein the ex-situ catalyst particles are in their final form prior to being deposited on the surface of the scaffold.
2. 2. The process of claim 1, wherein the surface of the static mixer is pre-coated with a support material and optionally a binder prior to step (i).
3. 3. The process of claim 1 or 2, wherein the catalytic liquid suspension further comprises a binder.
4. 4. The process according to any one of claims 1 to 3, wherein the process further comprises a pre-treatment step prior to applying the catalytic liquid suspension to the surface of the scaffold in step (i), the pre-treatment step comprising at least one surface treatment step on the surface of the scaffold selected from chemical treatment, anodizing, hot dip plating, vacuum plating, painting, thermal spraying, and acid etching.
5. The process of any one of claims 1 to 4, wherein the ex-situ catalyst particles are formed from a catalyst material or a catalyst support material comprising the catalyst material on a support material.
6. 6. The process of claim 5, wherein the catalytic material is selected from a metal, a metal oxide, an aluminum silicate, an activated carbon, a mesoporous carbon, a graphene, a graphitic material, a metal organic framework, a zeolite, or any combination thereof.
7. 7. The process of claim 6, wherein the metal is selected from at least one of aluminum, iron, cerium, calcium, cobalt, copper, magnesium, zinc, nickel, palladium, platinum, gold, silicon, silver, ruthenium, iridium, rhodium, titanium, vanadium, zirconium, niobium, tantalum, and chromium, or a metal oxide thereof.
8. 8. The process of any one of claims 2 to 7, wherein the support material is selected from at least one of activated carbon, mesoporous carbon, graphene, graphitic materials, metal organic frameworks, zeolites, aluminum oxide, silicon dioxide, ceramics, magnesium chloride, calcium carbonate, or dipotassium oxide.
9. 9. The process of any one of claims 5 to 8, wherein the catalyst support material is selected from at least one of ruthenium on aluminum oxide, palladium on aluminum oxide, lead-poisoned palladium on calcium carbonate, iron on aluminum oxide, silver on aluminum oxide, silica diphenylphosphine palladium, palladium on titanium silicate, palladium on carbon, nickel modified aluminum oxide, silicon oxide, or zeolite.
10. 10. The process of any one of claims 2 to 9, wherein the binder for the catalytic liquid suspension is selected from the group comprising hydroxypropyl cellulose, methyl cellulose, polyester, polyurethane, acrylic resin, condensation resin, polyvinyl acetate, sodium poly(acrylic acid), polyvinylidene fluoride, polyethylene oxide, polyethylene glycol, dextrin, sodium silicate, colloidal silica, polydimethylsiloxane, boehmite, colloidal aluminum oxide, or polyisobutylene.
11. The process of claim 10, wherein the binder is added at a concentration of between about 0.3% and about 5% by weight, based on the total weight of the catalytic liquid suspension.
12. The process of any one of claims 1 to 11, wherein the liquid carrier is selected from the group comprising water, ethanol, isopropanol, butanol, ethyl acetate, acetone, or combinations thereof.
13. The process of any one of claims 1 to 12, wherein the catalytic liquid suspension has a solids content of between about 3% and about 28% by weight.
14. The process of any one of claims 1 to 13, wherein the coating has a thickness between about 1 μm and about 50 μm.
15. The surface area of the catalyst is about 1 m 2 / g ~ approx. 1000m 2 The process of any one of claims 1 to 14, wherein the molar ratio is between 1 / g and 2 / g.
16. 16. The process of any one of claims 1 to 15, wherein the coating adhesion results in a total coating mass loss of less than about 0.5 wt. % as measured by ultrasonication testing.
17. The process of any one of claims 1 to 16, wherein the scaffold is a metal, a metal alloy, a cermet, carbon fibre, silicon carbide or a polymer.
18. 20. The process of claim 17, wherein the scaffold is a metal scaffold.
19. 20. The process of claim 18, wherein the metal or metal alloy of the metal scaffold is titanium, aluminum or stainless steel.
20. The process of any one of claims 1 to 19, wherein the ex-situ catalyst particles are less than about 5 μm.
21. The method of claim 20, wherein the drying step comprises the steps of: (a) applying a first temperature ranging between about 15° C. and about 30° C. to a surface of the coated scaffold for a first period of about 4 to 24 hours to volatilize at least a portion of volatile materials from the catalytic liquid suspension; (b) applying a second temperature in the range of between about 100° C. and about 180° C. under a controlled atmosphere for a second period of time of about 4 to 24 hours to form a dry coating on a surface of the scaffold; The process according to any one of claims 1 to 20, comprising:
Citation Information
Patent Citations
JP1975124891A
Hydrogen catalyst member
JP2015120135A
Static mixers for continuous flow catalytic reactors.
JP2019501764A